The Pathological Mechanism Between the Intestine and Brain in the Early Stage of Parkinson's Disease - Yang, Runing; Gao, Ge; Yang, Hui (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD) is the second most common chronic progressive neurodegenerative disease. The main pathological features are progressive degeneration of neurons and abnormal accumulation of α-Synuclein. At present, the pathogenesis of PD is not completely clear, and many changes in the intestinal tract may be the early pathogenic factors of Parkinson's disease. These changes affect the central nervous system (CNS) through both nervous and humoral pathways. α-Synuclein deposited in the intestinal nerve migrates upward along the vagus nerve to the brain. Inflammation and immune regulation mediated by intestinal immune cells may be involved, affecting the CNS through local blood circulation. In addition, microorganisms and their metabolites may also affect the progression of PD. Therefore, paying attention to the multiple changes in the intestinal tract may provide new insight for the early diagnosis and treatment of PD.